High purity separation of hypericin from Hypericum perforatum L. extract with macroporous resin column coupling preparative liquid chromatography. (April 2021) - Zhang, Jie; Feng, Chunrong; Ge, Pu; Wang, Qingqing; Liu, Yanling; Xu, Hui; Zhou, Xing
Graphical abstract: Highlights: The coupling process is an effective strategy to prepare high purity products. The total recovery ratio of hypericin was 80.6 % in the coupling process. Hypericin with the purity of 98.7 % was obtained from the extracts efficiently. XAD16 N column chromatography showed an excellent stability and reproducibility. Abstract: Hypericin has shown promising potential for the prevention and treatment of cancer. Here we report facile strategy for the separation and purification of natural products from the extracts by demonstrating hypericin isolation from Hypericum perforatum L. extract using macroporous resin column chromatography (MRCC) followed by preparative liquid chromatography (PLC). Effect of various parameters including the kinds of resins, loading extract concentration, loading flow rate, types of eluent, and elution flow rate on the separation efficiency of MRCC for hypericin was investigated. The purity and purification ratio of hypericin was 71.8 % and 2.4 respectively, optimized by XAD16 N MRCC with a high stability and reproducibility. PLC parameters were determined by optimizing stationary phase, mobile phase, and injection sample amount. The high purity hypericin (98.7 %) was achieved by PLC and the total recovery ratio of hypericin was 80.6 % in the coupling process.